Effect of feeding system on the growth and carcass characteristics of Iberian pigs, and the use of ultrasound to estimate yields of joints. - Daza, a; Mateos, A.; López Carrasco, C.; Rey, A.; Ovejero, I.; López-Bote, C. J. (Meat science, 2006)
Forty three-castrated male Iberian pigs of the Torbiscal line with an average initial weight of 102.27kg were used. A group of 22 pigs was fed according to the traditional way in free-range conditions with acorn and grass from November to January. Another group of 21 animals was fed 3.72kg/day of a conventional feed that contained 12.53MJME/kg, 16.21% crude protein, 4.94% fat and 6.64% of crude fiber, during the same period. Measurements of backfat thickness and Longissimus dorsi muscle area at the last rib were taken by means of a real-time ultrasound device (Kretz Technick Inc., 600 V-V2.32, Sonovet, Austria) in all pigs before slaughter. After slaughter, carcass, ham and foreleg weights and backfat and muscle area measurement from the last rib chop were recorded. The average daily gain, carcass yield, fat thickness, loin area, ham weight and proportion of hams were significantly higher (P<0.05) in the pigs fed in confinement than in those fed extensively (653.36g, 77.97%, 56.46mm, 3031mm(2), 22.26kg and 14.32% vs 501.48g, 76.94%, 51.74mm, 2673mm(2), 21.52kg and 13.79%, respectively). This paper shows the prediction equations for hams, forelegs and total hams and forelegs weights and proportions with respect to slaughter weight and live ultrasound measurements in pigs fed either extensively or in confinement. The ultrasound measurements better predicted the carcass cuts absolute amounts (R(2)=0.591-0.875) than the carcass cuts proportions (R(2)=0.23-0.40). The use of real-time ultrasound should be used with caution to predict the absolute quantities of hams and forelegs from Iberian pigs since the ultrasound measurements are only moderately accurate.
The following values have no corresponding Zotero field: accession-num: 22061368
Keywords: carcass; feeding; Growth; iberian pig; ultrasounds

Effect of feeding system on the growth and carcass characteristics of Iberian pigs, and the use of ultrasound to estimate yields of joints. (Meat science, 2006)
Forty three-castrated male Iberian pigs of the Torbiscal line with an average initial weight of 102.27kg were used. A group of 22 pigs was fed according to the traditional way in free-range conditions with acorn and grass from November to January. Another group of 21 animals was fed 3.72kg/day of a conventional feed that contained 12.53MJME/kg, 16.21% crude protein, 4.94% fat and 6.64% of crude fiber, during the same period. Measurements of backfat thickness and Longissimus dorsi muscle area at the last rib were taken by means of a real-time ultrasound device (Kretz Technick Inc., 600 V-V2.32, Sonovet, Austria) in all pigs before slaughter. After slaughter, carcass, ham and foreleg weights and backfat and muscle area measurement from the last rib chop were recorded. The average daily gain, carcass yield, fat thickness, loin area, ham weight and proportion of hams were significantly higher (P<0.05) in the pigs fed in confinement than in those fed extensively (653.36g, 77.97%, 56.46mm, 3031mm(2), 22.26kg and 14.32% vs 501.48g, 76.94%, 51.74mm, 2673mm(2), 21.52kg and 13.79%, respectively). This paper shows the prediction equations for hams, forelegs and total hams and forelegs weights and proportions with respect to slaughter weight and live ultrasound measurements in pigs fed either extensively or in confinement. The ultrasound measurements better predicted the carcass cuts absolute amounts (R(2)=0.591-0.875) than the carcass cuts proportions (R(2)=0.23-0.40). The use of real-time ultrasound should be used with caution to predict the absolute quantities of hams and forelegs from Iberian pigs since the ultrasound measurements are only moderately accurate.